Laparoscopic Mitrofanoff procedure in children: Critical analysis of difficulties and benefits. Issue 1 (February 2015) - Blanc, Thomas; Muller, Cécile; Pons, Maguelonne; Pashootan, Pourya; Paye-Jaouen, Annabel; El Ghoneimi, Alaa
Summary Objectives The Mitrofanoff principle is an accepted continent urinary diversion. We studied the feasibility and the possible benefits of using a laparoscopic approach in children with significant bladder dysfunction associated with difficulty doing efficient urethral catheterization. Patients and methods A fully laparoscopic Mitrofanoff continent cystostomy was attempted in 15 children with a median age of 9 years (IQR 6), between 2003 and 2013. Before the Mitrofanoff procedure was considered, urodynamic evaluation was done for each patient, to study bladder compliance, detrusor activity, and bladder capacity. The procedure was performed using a transperitoneal four-port approach. A 30-degree down camera angle was optimal for viewing the appendix and the posterior wall of the bladder. The operative steps of the open procedure were replicated laparoscopically. The proximal end of the appendix was spatulated and anastomosed to the posterior wall of the bladder, providing an antireflux mechanism by an extramucosal tunnel. The distal end of the appendix was brought out as the cutaneous umbilical stoma. Some modifications were done because of the high rate of conversion due to early opening of the mucosa (harmonic hook) or difficult anastomosis: (a) use of 5-mm trocars to change the laparoscope position from the left to right subcostal area to better visualize the anastomosis, (b) the anastomosis was suspended at its two ends during suturing; a trans-abdominal traction suture of the bladder was inserted for better exposure of the anastomosis (hitch stitch) and to stabilize the anastomotic line during suturing, (c) use of a monopolar hook to cut the detrusor muscle fibers, to avoid incidental opening of the mucosa, and (d) the window between the appendix and the peritoneum was closed to avoid internal hernia. Results The procedure was totally completed by laparoscopy in 12 cases. Three were converted to an open procedure due to tearing of bladder mucosa (n = 2) or appendix ischemia (n = 1). Median operative time for fully laparoscopic Mitrofanoff was 255 min (IQR 52). Median follow-up was 18 months (IQR 35). No patient required stomal revision. Seven patients were continent, five experienced urinary leakage from urethra n = 1 and/or stoma n = 5. Three patients with stomal urinary leakage were successfully managed by Deflux (dextranomer-based implants) injection in the catheterizable channel. Two patients required an open revision of the appendicovesical anastomosis. The patient with both stomal and urethral urinary leakage also required the implantation of an artificial urinary sphincter 1.5 years after Mitrofanoff. One patient had bladder augmentation. Conclusion Although our results of laparoscopic Mitrofanoff procedure in children are unsatisfying in cases of high-pressure bladders in terms of incontinent stoma, we still believe that it is justified to develop this challenging technique with more refinement and improvement, to provide a minimal invasive procedure that may postpone or even avoid bladder augmentation in pediatric age.